2007
DOI: 10.1097/opx.0b013e31815b9dec
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Photophobia After Surgical Treatment in Intermittent Exotropia

Abstract: The angle of strabismus and stereoacuity were found to affect the occurrence of binocular photophobia. Successful surgery treated binocular photophobia in 53.5% of patients. Regardless of the surgical result, clinicians should educate patients in terms of the possibility of persistence of postsurgical photophobia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 2 publications
1
12
0
2
Order By: Relevance
“…The rate of remission of photophobia after surgery was 57.2% in one report, 12 which was similar to the rates of improvement in squinting or photophobia after surgery in the present report (64.8 or 59.4%, respectively). They also reported that age, sex, and angle of deviation at a distance and a near range were not associated with the disappearance of photophobia in the satisfactory group, which was defined as a postoperative angle of deviation less than 10 PD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The rate of remission of photophobia after surgery was 57.2% in one report, 12 which was similar to the rates of improvement in squinting or photophobia after surgery in the present report (64.8 or 59.4%, respectively). They also reported that age, sex, and angle of deviation at a distance and a near range were not associated with the disappearance of photophobia in the satisfactory group, which was defined as a postoperative angle of deviation less than 10 PD.…”
Section: Discussionsupporting
confidence: 90%
“…10,11 Another study showed that a large preoperative angle of deviation and decreased stereopsis were associated with binocular photophopia. 12 However, the detailed features of exotropia were not included in that investigation. In addition, ''squinting'' and ''photophobia'' were considered as equivalent concepts in these studies.…”
mentioning
confidence: 99%
“…(Wang & Chryssanthou, 1988) Lew et al found that a majority of patients with intermittent XT exhibit photophobia and that surgical correction alleviates this symptom in many patients. (Lew et al, 2007) We previously made the preliminary observation in a subset of the current cohort that the primary concern of children with intermittent XT appeared to be closure of one eye in sunlight. (Hatt et al, 2010b) Our current study confirms this finding in a larger cohort.…”
Section: Discussionmentioning
confidence: 96%
“…This symptom affects the patient's health-related quality of life, 3 and it often persists even after successful strabismus surgery. 4 Several studies have suggested that the mechanism of TEC is a decreased threshold of bright light, abnormal binocular summation, diplopia, or Fechner's paradox, which is, in brief, the apparent increase in the brightness of a gure caused by closing one eye after viewing the gure with both eyes open. [4][5][6][7] Although many studies considered TEC and photosensitivity as synonyms, 6,8−10 the association between TEC and photosensitivity is still unclear.…”
Section: Introductionmentioning
confidence: 99%